Autonomous Health Movements: Criminalization, De-Medicalization, and Community-Based Direct Action - Naomi Braine (Harvard FXB Center for Health and Human Rights, 2020)
This paper proposes the concept of autonomous health movements, drawing on an analysis of harm reduction in the United States and self-managed abortion globally. Harm reduction and self-managed abortion appear in the professional literature largely as evidenced-based public health strategies, more than as social movements. However, each began at the margins of the law as a form of direct action developed by activists anchored in social justice movements and working in community contexts independent of both state and institutional control according to a human rights perspective of bodily integrity and autonomy. An analysis of the history and dynamics of harm reduction and self-managed abortion as social movements underlies the proposed framework of autonomous health movements, and additional potential examples of such movements are identified. The framework of autonomous health movements opens up new pathways for thinking about the development of autonomous, community-based health strategies under conditions of marginalization and criminalization.